Perbandingan Kinerja Algoritma Elias Delta Code Dan Algoritma Punctured Elias Code Dalam Kompresi File Teks - Arlansyah Tanjung (STMIK Budi Darma, 2022)
The problem of data size is an important problem in the data exchange process. In particular, text files are relatively large files. Large data sizes create constraints for data management, such as the need for large storage space and long transmission times. To overcome these problems it is necessary to apply compression techniques. Users can import text files to be compressed as well as choose a compression algorithm. In this research, Elias Delta Code and Punctured Elias Code algorithms are applied to compress text files and then compare their performance based on the set parameters. After implementing and testing the system, it can be seen that the Elias Delta Code algorithm has better performance than the Punctured Elias Code algorithm in text file compression with the final value using the Exponential Comparison Method, the Elias Delta Code algorithm with a final value of 6.526 while the Punctured Elias Code algorithm 6.653, So the higher the total value obtained, the higher the amount of work done by the algorithm. Based on this analysis, the Elias Delta Code Algorithm which is the algorithm has the best performance in text file compression.